Energy transition calls for high investment - Jürgen Blazejczak; Jochen Diekmann; Dietmar Edler; Claudia Kemfert; Karsten Neuhoff; Wolf-Peter Schill (DIW Economic Bulletin, 2013)
Achieving the objectives of the German governments 2010 Energy Concept and the accelerated phase-out of nuclear energy will require significant investment in restructuring energy supply. In particular, this includes investment in installations for the use of renewable energy sources in the power and heating sector, as well as in the infrastructure, such as power grids. In addition, substantial investment is needed to improve energy efficiency, for example, by insulating buildings. Model calculations by DIW Berlin show that the transformation of the energy sector is likely to have a sustained positive effect on added value in Germany. Furthermore, this investment will lead to substantial savings of primary fossil energy sources. This is also accompanied by a reduction in energy-related greenhouse gas emissions. The existing framework for investment in renewable power generation and electricity grids is largely appropriate and should, in principle, be maintained in the near future. Accelerating the rate of the energy-efficient building refurbishment, however, will require additional incentives.
Keywords: Q42; Q43; Q48; Q52; 330; energy transition; investment; renewable energy; energy efficiency